Toxicological evaluation of Carthamus lanatus L (Carthame laineux) hydro-alcoholic extract in Wistar rats: acute oral toxic effects - Akram, Melakhessou Mohamed (2024)
Background: Despite the well-known phytotherapeutic properties of Carthamus lanatus L in traditional medicine, there is little evidence on its toxicity profile in hematological and biochemical parameters. Objective: This study was intended to evaluate the acute toxicity effect of Carthamus lanatus L. Methods: The toxicological impact of a hydroalcholic extract of Carthamus lanatus (HAECL) at 200, 400, and 800 mg/kg body weight on hematological indices in rats was assessed gradually at 24 hours after 1, 10, and 14 days. Results: We observed no significant difference in the consumption of food, body weight, or relative organ weights. Hematological and biochemical parameters revealed the non-adverse effects of prolonged oral consumption of Carthamus lanatus except for a slight increase but no significant increase in ASAT and ALAT and a no significant decrease in the percentage of basophils. Conclusions: These data imply that the extract has a non-hematotoxic potential. Overall, the impact of carthamus lanatus extract in this study shows that it is unlikely to be hematotoxic and might be a promising candidate in the treatment of coronary heart disease if taken at the levels tested.